The results of deep magnetotelluric sounding on profile Quan Son - Quan Hoa in the province Thanh Hoa - Son, Vo Thanh; Minh, Le Huy; Marquis, Guy; Thanh, Nguyen Ha; Hao, Truong Quang; Vinh, Nguyen Ba; Quyen, Dao Van; Thang, Nguyen Chien (Vietnam Journal of Earth Sciences, 2015)
In 2013 the 12 stations of deep magnetotelluric sounding (MT) by Geo-instrument (made in France) on the profile about 25 km of long in the Quan Son - Quan Hoa districts of province Thanh Hoa has been carried out. The data was processed and 2D modeled by Geotools software. The obtained 2D resistivity cross-section until 30 km of depth represents structural features of earth crust here: High resistivity in the upper part of section until 10 -15 km of depth, indicates the consolidated rocks; low resistivity is distributed in lower part of section may be reflects the rock containing water relating to tectonic - geodynamic conditions, geothermal regime of earth’s crust. Two low resistivity zones in center of profile with vertical development lightly indicate the Songma and the Sopcop - Quanson faults respectively, their positions are coincided with the distributions of these faults on the geological map. References Cagnia L., 1953: Basic theory of magnetotelluric method of geophysical prospecting, Geophysics, 18, 605-635. Geotools Corporation, 1997: Geotools MT User’s guide. Ingham M., 2005: High resolution electrical imaging of faults zones, Phys. Earth Planet. Inter., 150, 93-105. Jones A., 1992: Electrical conductivity of the continental lower crust Continental lower Crust, edited by D. M, Fountain, R. J. Arculus and R. W. Kay. Lê Huy Minh, Đinh Văn Toàn, Võ Thanh Sơn, Nguyễn Chiến Thắng, Nguyễn Bá Duẩn, Nguyễn Hà Thành, Lê Trường Thanh, Guy Marquis, 2011: Kết quả xử lý bước đầu số liệu đo sâu từ tellua tuyến Hòa Bình – Thái Nguyên và tuyến Thanh Hóa - Hà Tây. Tạp chí các Khoa học về Trái Đất, 33(1), 18-28. Pham V. N., Boyer D., Nguyen Van Giang et Nguyen Thi Kim Thoa, 1995: Propriétés électriques et structure profonde de la zone de faille du Fleuve Rouge au Nord Vietnam d’après les résultats de sondage magnéto-tellurique, C. R. Acad. Sci. Paris, 320, série IIa, 181-187. Quomarudin M., 1994: Propriétés électriques et structures de la croûte en France, (Programmes Ecors, GPF) d’après les résultats de sondage magnéto-tellurique, Thèse, Université Paris 7. Smith J. T. & Booker J. R., 1991: The rapid relaxation inverse for two and three dimensional magnetotelluric data, J. Geophys. Res., 96, NO. B3, 3905-3922. Touret J. L. R. et Marquis G., 1994: Fluides profondes et conductivité électrique de la croûte continentale inférieure, C. R. Acad. Sci. Paris, 318, Série II, 1469-1482. Đoàn Văn Tuyến, Đinh Văn Toàn, 2011: Đặc điểm cấu trúc độ dẫn điện và mối quan hệ với dị thường địa nhiệt ở đới đứt gãy Sông Hồng. Tạp chí Các Khoa học về Trái Đất, 33(2), 10-17. Đoàn Văn Tuyến, Đinh Văn Toàn và Nguyễn Trọng Yêm, 2001: Đặc điểm cấu trúc địa động lực đới đứt gãy Sông Hồng trên cơ sở tài liệu từ telua. Tạp chí Địa chất, A267, 21-28. Vozoff K., 1972: The magnetotelluric method in the exploration of sedimentary basin. Geophysics, 37, No 1, 98-141.